(untitled) (MAUSAM, 2025)
The rainfall analysis is helpful for proper crop planning under changing environment in any region. Therefore in this study an attempt has been made to analyze long term rainfall data, i.e., 40 years from 1981-2020 (Tarai region) and 36 years from 1985-2020 (mid Himalayan region) as per availability and comparison is being done on the type of crop to be grown, sowing time, irrigation scheduling etc. The initial and conditional probability of rainfall on weekly basis was analyzed at different levels, i.e., >5mm, >10mm, >20mm, >30mm, >40mm and >50mm using Markov chain model. In addition to this, incomplete gamma distribution was also used to find out the occurrence of rainfall events at different probability levels, i.e., 10, 25, 50, 75 & 90 per cent. The results revealed that though the amount of rainfall in the Tarai region is higher when compared with mid Himalayan region but most of them is limited to southwest monsoon season only. The crops can be raised easily throughout the year in the mid Himalayan region because of uniform distribution of rainfall in all the seasons except in the post monsoon season year and by arranging lifesaving irrigation to growing crops during light/moderate/severe dry spells conditions only from available natural springs/perennial streams/harvesting run off water during the water stress weeks. On the other hand, in the Tarai region proper irrigation facilities must be ensured during all the seasons except in the southwest monsoon season in order to have productive yield.